Konsep Pemberdayaan Daging Hewan Dam (Studi atas Fatwa Majelis Ulama Indonesia) - Robingun Suyud El Syam; Abdul Basir (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2022)
The management of the pilgrimage is essentially a form of service to the community. Indonesian pilgrims are accustomed to performing the Tamattu Hajj because they come to the Holy Land before the Hajj. it is even mentioned that almost 99 percent, so that you have to pay for the dam, among others, by slaughtering a goat. In the usual management, dam animal meat can only be enjoyed by the poor in Saudi Arabia, because the slaughter is carried out there so it is difficult to distribute it to the poor in Indonesia, as advised by the MUI. In order for this moral message to be realized, it is necessary to take another MUI fatwa option regarding the preservation and distribution of sacrificial meat in processed form, namely processed and preserved, such as canned and processed in the form of corned beef, rendang, or the like. The assumption is that although qurban and dam are different, the distribution is the same for the poor. In addition, the breakthrough "application of the distribution of dam meat" is a meeting point, dam meat can be felt by the poor in Indonesia.